Agroforestry Practices for Food-Fuel Security in Rainfed Agroecosystem : A Management Option - Upadhyaya, S.D.; Nema, Sharad; Bhargava, M. K. (Indian Journal of Agroforestry, 2020)
A detailed survey of Kymore plateau and Satpura hills agroclimatic zone (the Kymore Plateau region delineates Jabalpur, Katni, Maihar, Satna and Rewa district) of Madhya Pradesh was carried out during 2001 and 2002 to delineate and map the area under Acacia-rice agroforestry system. Study suggested that tree canopy management with different pruning intensity on high (more than 25 trees/ 100 running meter of bund), medium (25 trees/ 100 running meter of bund) and low (less than 25 trees/ 100 running meter of bund) density of trees on farm bunds not only improve the light infiltration but significantly increases the yield of wheat and rice by ameliorating the bio-physical environment. The optimum yield was obtained under 40 per cent canopy pruning intensity. Hence the maintenance of 60 per cent Live Crown Ratio (LCR) can be recommended as appropriate for wheat and rice growth and yield grown below the canopy of Acacia nilotica which also provides valuable fuelwood and non-woody biomass additionally to the farmers. Scientific data on silvicultural characters of Acacia nilotica and its effect on rice yield, soil productivity have been investigated to determine the effectiveness, sustainability and socio-economic acceptability of the system and it seems to be a viable option that can provide food-fuel and livelihood security to the rural work force on an ecologically sustainable basis specifically in rainfed agroecosystem.